Predatory efficacy of Bdellovibrio stolpii isolated from the wastewater sources against the multidrug-resistant clinical isolates. (23rd January 2023) - Suresh, Manikeri Shraddha; Rai, Dhanyashree; Raj, Juliet Mohan; Premanath, Ramya; M, Divyashree
Abstract: The present study investigated the predatory efficacy of Bdellovibrio isolated from untreated hospital wastewater sources against human pathogens. Bdellovibrio is a Gram-negative, motile, uniflagellate predatory bacteria present in the environment, which directly predates on other bacteria, including human pathogens. In the present study, 30 hospital effluent samples were collected and screened for Bdellovibrio . A total of 11 Bdellovibrio isolates were obtained by the double-layer agar technique. All the isolates were identified by amplification of the 16S rDNA coding region using polymerase chain reaction (PCR) and confirmed as Bdellovibrio stolpii . The lytic activity of confirmed isolates was investigated against four Gram-negative bacteria Pseudomonas aeruginosa ADW44, Pseudomonas aeruginosa 27853(ATCC Strain), V. cholerae and Salmonella typhimurium of clinical origin obtained from the institutional repository. Among the 11 isolates, three Bdellovibrio isolates NBd1, YBd1 and RBd1 demonstrated the ability to prey upon the tested clinical isolates. To the best of our knowledge, this is the first report on the isolation of B. stolpii from hospital wastewater settings in India with broad and high bacteriolytic activity. HIGHLIGHT: Antibiotic resistance in bacteria is a major concern in both national and international scenarios. The study gives insights into the predatory spectrum of Bdellovibrio, against multidrug-resistant bacteria. The present study may help in the development of Bdellovibrio as a whole-organism approach against biofilm-forming bacteria. Developing more efficient, economic, and environmentally friendly biocontrol agents against multidrug-resistant bacteria is the need of the hour. Graphical Abstract